TRANSLATION OF GERMAN-LANGUAGE VEHICLE REGISTRATION DOCUMENTS IN THE LIGHT OF LINGUISTIC PLURICENTRISM - KUBACKI, Artur Dariusz (Comparative Legilinguistics, 2018)
The author analyses the translation of vehicle registration documents issued in Germany, Austria and Switzerland in the light of linguistic pluricentrism. German-language vehicle registration documents, belonging to the genre of official documents, are examined from the point of view of their function, linguistic structure and translation problems which may appear while translating them into Polish. The translation of LSP texts in the context of pluricentrism of the German language has rarely been the subject of scientific analyses. In the theoretical part of the article, the author generally characterizes linguistic pluricentrism and Polish contrastive studies in that respect. In the practical part of the article, he discusses vehicle registration documents as a specific type of official documents, shortly describes them functionally and linguistically and considers translation problems connected with these documents from the perspective of linguistic pluricentrism. Finally, he indicates mistakes in the translation of Austrian vehicle registration documents made by a sworn translator of German.